Dampak Work-Life Balance Karyawan Terhadap Kinerja Melalui Organizational Citizenship Behavior - Ahadiati Rohmatiah; Mukti Widodo; Mutmainah Mutmainah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
Background – Companies that pay attention to the work-life balance of employees will improve performance and cause organizational citizenship behavior. Work-life balance and organizational citizenship behavior of employee can one of factors to impact their performance. So, its can impact to corporate image in society. Aim – This study aims to determine the influence of work - life balance and organizational citizenship behavior on employee performance, the influence of organizational citizenship behavior on employee performance, and the influence of work-life balance on employee performance of Bank Jatim Madiun Branch Office through organizational citizenship behavior as a mediating variable Design / methodology / approach – The research population is all employees of the Bank Jatim Madiun Branch Office in 2022, totaling 141 people. Sample of 59 people was obtained which was determined by simple random sampling technique. The research instrument used a questionnaire. The data analysis technique uses path analysis method with SmartPLS version 3.0 software. Findings – The results showed: 1) Work-life balance affects the performance of employees of Bank Jatim Madiun Branch Office, 2) Work-life balance affects organizational citizenship behavior of employees of Bank Jatim Madiun Branch Office, 3) Organizational citizenship behavior affects the performance of employees of Bank Jatim Office Madiun Branch, 4) Work-life balance affects the performance of Bank Jatim Madiun Branch Office employees through organizational citizenship behavior as a mediating variable. Conclusion - The test variables in this article have a significant influence and can explain these conditions in the internal environment of the Bank Jatim Madiun Branch Office. Research implication – This research add knowledge about factors of employee performance. So, this result can reference for entrepreneur to more pay attention their employee, especially work-life balance and organizational citizenship behavior of employee. Both of them can concerned to increasing and optimizing performance of employee continually. Limitations – This research only examine about work-life balance, organizational citizenship, and employee performance in Bank Jatim Madiun Branch Office.